Comparison of air quality standards between Brazil and countries from the five continents - Amaral, Carlos Henrique Cordeiro de; Rêgo, Rita de Cássia Franco; Northcross, Amanda Laura (Sustainability in Debate, 2023)
This article presents a comparative study of air quality regulations. The main objective was to compare Brazil’s current technical air quality standards with international standards. The air quality standards defined by Brazil for PM2.5, PM10, lead, SO2, NO2, and O3 have higher values than international norms, and Brazil lacks standards for important pollutants like mercury, cadmium, nickel, toluene, and PAHs. The use of more permissive air quality standards significantly distorts the perception of potential exposure for the population, downplaying the actual impact on public health, leading to inadequate public health planning, and resulting in avoidable hospitalisations, premature deaths, and other intangible costs like reduced quality of life for the population.